Learners’ perceived advantages and social-affective dispositions toward online peer feedback in academic writing - Zhang, Meng; He, Qiaoling; Du, Jianxia; Liu, Fangtong; Huang, Bosu (Frontiers in Psychology, 2022)
Peer feedback is widely acknowledged for its advantages and benefits in improving students’ learning in writing classes. Although the integration of online platforms has been found to impact peer feedback, research on second language learners’ perceived advantages and social affective disposition to using multiple platforms for delivering peer feedback is limited. To address the aforementioned research gap, we conducted this 12-week action research to explore how 12 doctoral students at a university in Macau perceived their experience of using multiple online feedback in an academic writing course. To integrate the various advantages of different online platforms, we adopted three tools including Moodle, Rain Classroom, and WeChat for the delivery of peer feedback. The results demonstrated learners’ perceived advantages and disadvantages of online peer feedback and how the different online peer feedback can be combined to magnify their benefits for academic writing. It also revealed that the use of emojis, memes, and one-to-one conversation window on WeChat can foster students’ positive emotions. However, the ubiquitous connection by WeChat Moments increased their emotional load and undermined peer trust.